PH variations during diafiltration due to buffer nonidealities. (4th September 2017) - Baek, Youngbin; Yang, Deyu; Singh, Nripen; Arunkumar, Abhiram; Ghose, Sanchayita; Li, Zheng Jian; Zydney, Andrew L.
Abstract : Diafiltration is used for final formulation of essentially all biotherapeutics. Several studies have demonstrated that buffer/excipient concentrations in the final diafiltered product can be different than that in the diafiltration buffer due to interactions between buffer species and the protein product. However, recent work in our lab has shown variations in solution pH that are largely independent of the protein concentration during the first few diavolumes. Our hypothesis is that these pH variations are due to nonidealities in the acid‐base equilibrium coefficient. A model was developed for the diafiltration process accounting for the ionic strength dependence of the pKa . Experimental results obtained using phosphate and histidine buffers were in excellent agreement with model predictions. A decrease in ionic strength leads to an increase in the pKa for the phosphate buffer, causing a shift in the solution pH, even under conditions where the initial feed and the diafiltration buffer are at the same pH. This effect could be eliminated by matching the ionic strength of the feed and diafiltration buffer. The experimental data and model provide new insights into the factors controlling the pH profile during diafiltration processes. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:1555–1560, 2017